FACTORS CAUSING RECIDIVISM IN CLASS IIA CURUP CORRECTIONAL INSTITUTION - Zhafran Al Farras; Mulyani Rahayu (Journal of Management Small and Medium Enterprises (SMEs), 2026)
This study aims to identify the factors causing recidivism and to analyze the pattern of inmate development at the Class IIA Correctional Institution in Curup. Using a descriptive qualitative approach, data were collected through interviews, observations, and documentation involving recidivist inmates and correctional officers. The findings indicate that recidivism is influenced by both internal and external factors. Internal factors include weak self-control, low legal awareness, and continued attachment to negative environments. External factors involve economic pressure, social stigma, and the absence of an effective reintegration system after release. The institution implements development programs focused on personality and independence. However, these programs have not been fully optimal due to limited facilities and a shortage of qualified coaches. The analysis is supported by Life Course Theory and Growth Mindset Theory, which emphasize the importance of life turning points and the development of a growth-oriented mindset in preventing reoffending. The study concludes that more comprehensive and sustainable approaches are needed. It recommends the development of psychosocial-based coaching programs and stronger reintegration partnerships involving multiple stakeholders to effectively reduce recidivism and support long-term behavioral change among inmates. Keywords: Recidivism; Correctional; Prisoner Coaching